2011
DOI: 10.1111/j.1460-9568.2011.07731.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of steroidogenic enzymes in the brain of adult zebrafish

Abstract: The brain of adult teleost fish exhibits several unique and interesting features, notably an intense neurogenic activity linked to persistence of radial glial cells acting as neural progenitors, and a high aromatase activity supported by strong expression of the cyp19a1b gene. Strikingly, cyp19a1b expression is restricted to radial glial cells, suggesting that estrogens are able to modulate their activity. This raises the question of the origin, central or peripheral, of C19 androgens available for aromatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 40 publications
10
94
1
5
Order By: Relevance
“…This suggests that the developmental loss of brain Hsd11b2 observed in higher vertebrates may not occur in fish, while the functional relevance of this observation from an evolutionary standpoint awaits further study. Interestingly, the pattern of hsd11b2 expression in the brain reported in this study parallels the distribution of key steroidogenic enzymes in the adult zebrafish brain (Diotel et al 2010(Diotel et al , 2011, including prominent expression in the telencephalon (Fig. 3A) and peripheral edges of the brain (Fig.…”
Section: Distribution and Functional Implicationsmentioning
confidence: 63%
“…This suggests that the developmental loss of brain Hsd11b2 observed in higher vertebrates may not occur in fish, while the functional relevance of this observation from an evolutionary standpoint awaits further study. Interestingly, the pattern of hsd11b2 expression in the brain reported in this study parallels the distribution of key steroidogenic enzymes in the adult zebrafish brain (Diotel et al 2010(Diotel et al , 2011, including prominent expression in the telencephalon (Fig. 3A) and peripheral edges of the brain (Fig.…”
Section: Distribution and Functional Implicationsmentioning
confidence: 63%
“…Our laboratory recently demonstrated that the brain of adult zebrafish was able to de novo synthesize a wide variety of radiolabeled neurosteroids from [ 3 H]-pregnenolone. Among these locally-produced steroids, there are notably dehydroepiandrosterone (DHEA), androgens (i.e., testosterone), estrogens (i.e., estrone and 17b estradiol), progesterone and derivatives [51,55]. Such results clearly evidence that 17b-hsd, 3a and 3b-hsd, cyp17, 5a-reductase and cyp19a1b (AroB) are expressed and biologically active in the brain of adult zebrafish.…”
Section: De Novo Neurosteroids Synthesismentioning
confidence: 78%
“…While neurosteroids synthesis is widely documented in mammals, only few studies focused on de novo steroid synthesis in the brain of teleost fish [51][52][53][54][55] Such a feature raises the question of the origin, local and/or peripheral, of C19 androgens available for brain aromatization. Our laboratory recently demonstrated that the brain of adult zebrafish was able to de novo synthesize a wide variety of radiolabeled neurosteroids from [ 3 H]-pregnenolone.…”
Section: De Novo Neurosteroids Synthesismentioning
confidence: 99%
“…However, studies conducted over the past two decades have demonstrated that the central and peripheral nervous systems have the capacity of synthesizing steroids, the so-called ‘neurosteroids' [for reviews, see [1,2,3,4,5,6,7,8,9]. De novo formation of neurosteroids in the brain was originally demonstrated in mammals [10,11,12,13,14,15,16,17,18], and subsequently in birds [2,6,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35], amphibians [36,37,38,39,40,41,42,43,44,45,46,47] and fish [48,49,50,51]. Therefore, de novo synthesis of neurosteroids from cholesterol in the brain appears to be conserved across the subphylum vertebrata [1,2,3,4,5,6,7,8,9].…”
mentioning
confidence: 99%